Crawling home - Sabo, Angela Lucia, author; Levy, EJ, advisor; Carter, Genesea, committee member; Humphrey, Mike, committee member (Colorado State University. Libraries, 2022)
Crawling Home investigates the life of a young woman ready to disrupt the norms around her. The memoir follows the narrator backwards through time from the loss of her best friend at age nineteen, to her earliest school memories, acutely aware of the ways in which she stands out—from being labeled disruptive in class throughout elementary school, to feeling disruptive of social norms through later years as she is diagnosed with a chronic physical disorder brought on by womanhood. Through a series of essays, divided into four parts, the narrator grapples with loss of loved ones, loss of home, loss of security and trust, and the need for answers.
Keywords: creative nonfiction